PENINGKATAN KEMAMPUAN PENJUMLAHAN BILANGAN BULAT 1 SAMPAI 10MELALUI MEDIA PUZZLE PADA ANAK TUNAGRAHITA SEDANG KELAS 1V SLB - KAMIM, M. (Jurnal Pendidikan Khusus, 2016)
ABSTRACT            Based  on  observation   in  SLB ( extraordinary  school ) Darul Ulum  Jombang ,states  that  4 th graders who have  got average  mentally disablet got difficulties in mathematics  lesson  in the part  of adding numbers. The purpose of this study was to determine theincrease of ability in summation of integers from one to ten through the puzzle  media on average mental disability children in fourth grade in SLB Darul Ulum  Jombang. This research aims to implement  puzzle  media to  the  increasing  ability of  adding  integer numbers from 1 to 10 for average level mentally disabled of 4 th graders.          This   research   is  a   classroom   action    research   by   using   Kemmis   and  Taggart model Data collection technique is done by using observation and experiment. The  research was conducted  by using 2 cycles.Each  sycle  consists of  3 meetings. In 2 nd cycle 3 rd meeting ,it gets the result about increasing ability of adding integer numbers. Mathematics  teaching   and   learning   process  by using  puzzle  media  not  only  benefits to train or exercise the stability of counting but also become a applying media for mentally disablet of 4 th graders the ability of counting,but also becomes a playing media for mentally disabled of 4 th graders.          Therefore,it can be concluded that the counting ability in adding numbers increases if the  puzzle media is used. Keywords :  Puzzle media, Sum.